Data Management by Librarian for Academic and Research Perceptions - Posiyya, Anivireddy; Saikumar, K (International Journal of Psychosocial Rehabilitation, 2020)
The trending technologies moves forward in rapid manner by utilising the data intensive science and management, these are stimulated to libraries of academics, R and D’s (research & development), tends to helpful for faculty, students and researchers. In this investigation three studies have been reported: Data and investigation services (DIS) of Canadian libraries of academics, research modules of India, data library services of U.S practises and research data service policies in similar libraries. Outcomes shows that research data services currently not updated and not employee in libraries, but so many services are in the construction stage, technical developments are very less then informational DIS, DIS are servicing more applications for students, researchers and faculties. Most of the directors of libraries thought that, they offer more opportunities for staff, DIS related to skills grater then percentage of libraries, such services not sufficient for libraries. So librarian has given more opportunities to learn about campus and interferes the workshops, conferences. This type of improvement increases the utilizations of data resources from 70% to 93%, at final compare existed services with proposed model, conclude that this work archives more efficient for all organizations.